2001
DOI: 10.1002/ar.10025
|View full text |Cite
|
Sign up to set email alerts
|

In vivo surface strain and stereology of the frontal and maxillary bones of sheep: Implications for the structural design of the mammalian skull

Abstract: Does the skull of the sheep behave as a tube or as a complex of independent bones linked by sutures? Is the architecture within cranial bones optimized to local strain alignment? We attempted to answer these questions for the sheep by recording from rosette strain gauges on each frontal and maxillary bone and from single-axis gauges on each dentary of five sheep while they fed on hay. Bone structure was assessed at each rosette gauge site by stereological analysis of high-resolution radiographs. Structural and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 29 publications
(36 reference statements)
4
43
0
Order By: Relevance
“…Data sample The mandibular bone strain data analyzed for this study (Table·1) were recorded in three different laboratories in connection with other studies (Herring and Teng, 2000;Hylander et al, 1998;Liu et al, 2004;Liu and Herring, 2000a;Liu and Herring, 2000b;Rafferty, 2005;Ravosa et al, 2000;Ross and Hylander, 1996;Thomason et al, 2001;Williams, 2004). Data were available for 3084 chewing cycles from 31 individuals of 11 species, including seven species of primates (four anthropoid and three strepsirrhine species), as well as goats (Capra), horses (Equus caballus), alpacas (Lama pacos), and miniature pigs (Sus) (Table·1).…”
Section: Methodsmentioning
confidence: 99%
“…Data sample The mandibular bone strain data analyzed for this study (Table·1) were recorded in three different laboratories in connection with other studies (Herring and Teng, 2000;Hylander et al, 1998;Liu et al, 2004;Liu and Herring, 2000a;Liu and Herring, 2000b;Rafferty, 2005;Ravosa et al, 2000;Ross and Hylander, 1996;Thomason et al, 2001;Williams, 2004). Data were available for 3084 chewing cycles from 31 individuals of 11 species, including seven species of primates (four anthropoid and three strepsirrhine species), as well as goats (Capra), horses (Equus caballus), alpacas (Lama pacos), and miniature pigs (Sus) (Table·1).…”
Section: Methodsmentioning
confidence: 99%
“…For example, working and balancing mandibular bodies show opposite directions of bending because of the influence of the unilateral bite point. 18 Other groups, including many rodents, pigs, and higher primates, have some probability of occlusal contact occurring on the balancing side, and may even have a bilateral bolus and true bilateral chewing. Thus in pigs, mandibular and maxillary strains are identical on the working and balancing sides.…”
Section: Muscles Mastication and The Biomechanics Of The Skullmentioning
confidence: 99%
“…Numerous experimental studies have shown that sutures typically exhibit strain magnitudes that are an order of magnitude higher than those in the bones that they connect, and strains can be reduced or reoriented across sutures (Jaslow, 1990;Jaslow and Biewener, 1995;Rafferty and Herring, 1999;Herring and Teng, 2000;Metzger and Ross, 2001;Rafferty et al, 2003;Lieberman et al, 2004). The principal strain values recorded from the alligators in vivo are on average greater than those recorded from any other vertebrate cranial bones that have been extensively sampled (Hylander, 1979;Hylander and Johnson, 1992;Herring et al, 1996;Ross and Hylander, 1996;Hylander and Johnson, 1997;Herring and Teng, 2000;Ravosa et al, 2000;Ross, 2001;Thomason et al, 2001;Lieberman et al, 2004;Ross and Metzger, 2004). If sutural strain increases as a function of bone strain, the very high bone strain magnitudes recorded in this study predict extremely high sutural strains, suggesting that sutural morphology might be of great importance in the functioning of the Alligator skull, as it appears to have been in dinosaurs (Rayfield, 2005, this issue) and at least some mammals (Herring and Teng, 2000).…”
Section: Comparison Of Models and In Vivo Datamentioning
confidence: 99%